Naravovarstveno vrednotenje aviafavne ob Savi med Krškim in Jesenicami na Dolenjskem s predlogom novega mednarodno pomembnega območja (IBA) za ptice v Sloveniji - Denac, Damijan (Natura Sloveniae, 2009)
Inventory of avifauna was carried out in 2008 within a 32 km2 area of the SavaRiver between Krçko and Jesenice na Dolenjskem with the aim to evaluate the conservation importance of the area. Birds were counted twice on 25.3 km of line transects placed in three landscape types - woods, agricultural landscape, and mosaic. Breeding birds along the Sava River, with emphasis on common kingfisher Alcedo atthis and common sandpiper Actitis hypoleucos, and of water bodies of the area were surveyed, too. In total, 132 species were recorded, 88 of which were breeders. Fifteen breeders are listed in Annex 1 ofthe Council Directive 79/409/EEC on the conservation of wild birds. Three ofthem meet the criteria for IBA/SPA designation - night heron Nycticorax nycticorax, black kite Milvusmigransand common kingfisher Alcedo atthis. The criteria used were: (1) more than 1% of the national breeding population of the species in the area, (2) more than two breeding pairs of the species in the area and more than five breeding pairs comprising the total national population, (3) for the qualifying species, five most important areas for the species in the region (Slovenia) can be proposed at the most. The proposed newIBA/SPA Sava river between Krško and Jesenice na Dolenjskem is the only area for the night heron and black kite and the fourth most important area forthe common kingfisher in Slovenia.
Keywords: bird; Birds; Classification; Dolenjska; Ecosystem; Ekosistem; ekosistemi; gnezdenje; Gnezdenje živali; Lower Carniola; Nesting Behavior; Populacijska gostota; Population Density; Ptice; Sava